PSSS - Process to Support Software Security - Nunes, Francisco José Barreto; Belchior, Arnaldo Dias (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2008)
Software security becomes very important to organizations that depend on or whose customers demand software products that assure information integrity, availability, and confidentiality. Unfortunately, despite the investments made in process improvement according to Software Engineering practices, there is still no guarantee that the developed software products are immune to attacks or do not present security problems. This paper presents a software security approach based on a specialized process to help develop more secure software products, entitled Process to Support Software Security (PSSS). In addition, this paper presents the results of the PSSS’s application in a software development project.